A Critical Review of the Arsenic Uptake Mechanisms and Phytoremediation Potential of Pteris vittata - Danh, L.; Truong, P.; Mammucari, R.; Foster, Neil (2014)
The discovery of the arsenic hyperaccumulator, Pteris vittata (Chinese brake fern), has contributed to the promotion of its application as a means of phytoremediation for arsenic removal from contaminated soils and water. Understanding the mechanisms involved in arsenic tolerance and accumulation of this plant provides valuable tools to improve the phytoremediation efficiency. In this review, the current knowledge about the physiological and molecular mechanisms of arsenic tolerance and accumulation in P. vittata is summarized, and an attempt has been made to clarify some of the unresolved questions related to these mechanisms. In addition, the capacity of P. vittata for remediation of arsenic-contaminated soils is evaluated under field conditions for the first time, and possible solutions to improve the remediation capacity of Pteris vittata are also discussed. © 2014 Copyright Taylor and Francis Group, LLC.